Percutaneous endoscopic gastrostomy tube placement in patients with head and neck cancer treated with radiotherapy - Uzun-Lang, Kristin; El-Shafie, Rami; Akbaba, Sati; Koschny, Ronald; Bougatf, Nina; Bernhardt, Denise; Welte, Stefan Ezechiel; Adeberg, Sebastian; Häfner, Matthias; Plinkert, Peter K.; Debus, Jürgen (Cancer management and research, 2020)
Background and aim: The primary aim of our study was to evaluate percutaneous endoscopic gastrostomy (PEG) tube placement depending on body weight and body mass index in patients undergoing radiotherapy (RT) for head and neck cancer (HNC). A secondary aim was to evaluate the course of weight change following PEG placement. Methods: We retrospectively reviewed the medical records of 186 patients with HNC undergoing radiotherapy (RT) or chemoradiotherapy (CRT) at our institution between January 2010 and August 2017. Initial weight and nutritional intake were analyzed prior to RT initiation and then followed throughout treatment until completion. Based on these data, the indication of PEG placement was determined. Medical records were also reviewed to analyze PEG-related acute toxicities. Results: A total of 186 patients met inclusion criteria. Patients were most commonly male (n=123, 66.1%) with squamous cell carcinoma (n=164, 88.2%). Patients who had dysphagia prior to treatment initiation as well as patients with a BMI 2 needed PEG placement earlier during the treatment course. Low-grade toxicities related to PEG insertion were observed in 10.7% patients, with peristomal pain and redness adjacent to the PEG tube insertion site being most common. High-grade toxicities, such as peritonitis and organ injury, were found in 4.9% of patients. Conclusion: Underweight patients and those with preexisting dysphagia should be closely screened during RT for weight loss and decreased oral intake. For weight loss greater than 4.5% during the treatment of HNC, early PEG-tube placement should be considered. Further prospective studies are needed to confirm these findings, and delineate a scoring system for timing of PEG use (prophylactic vs reactive) as well as assess the quality of life in patients with HNC who receive PEG placement.
Gesehen am 20.01.2020